2019
DOI: 10.3390/ijerph16204043
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Antecedents of Organic Food Consumption in Pakistan: Moderating Role of Food Neophobia

Abstract: Environmental and health problems have increased the interest of researchers and practitioners in investigating the factors that affect organic food consumption. However, little attention has been paid to the actual organic food buying behavior, particularly in developing countries like Pakistan. Therefore, the aim of the present study is to determine the actual buying patterns of consumers. For this purpose, a conceptual model based on green perceived value framework which predicts consumer’s purchase intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 98 publications
(143 reference statements)
3
78
4
3
Order By: Relevance
“…Thus, the best way is to measure the predictive relevance Q 2 of the model. If the value of Q 2 is higher than zero, then latent exogenous paradigms have great predictive relevance [93]. The results show that the value of Q 2 is 0.237 for farmers' adoption intentions, which suggests that the model has significant predictive relevance.…”
Section: Structural Modelmentioning
confidence: 85%
“…Thus, the best way is to measure the predictive relevance Q 2 of the model. If the value of Q 2 is higher than zero, then latent exogenous paradigms have great predictive relevance [93]. The results show that the value of Q 2 is 0.237 for farmers' adoption intentions, which suggests that the model has significant predictive relevance.…”
Section: Structural Modelmentioning
confidence: 85%
“…Therefore, an opportunity exists to explore the effects of industrial life cycle on the economic indicators of the country. Finally, some researchers, such as Hair et al [61], Akbar et al [62], Wang et al [63], and Ali et al [64] suggested an emerging statistical technique, partial least squares structural equation modelling (PLS-SEM) to be applied on different types of datasets in order to obtain interesting findings. Thus, it would be fascinating to apply PLS-SEM in the literature on FLC to bring about some new insights.…”
Section: Discussionmentioning
confidence: 99%
“…Situational influences (COVID-19) were measured by five items adopted by Nguyen et al [96]. Similarly, items for OFDO service adoption were constructed by Akbar et al [78], and Yadav and Pathak [106]. All items capturing the constructs were measured by adopting a seven-point Likert scale, which ranged from (1) strongly disagree to (7) strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Wang, Law, Guillet, Hung, and Fong [73] stated that intention is the willingness of a consumer to direct their attention to participating in exploring the appropriate information and in choosing the desired products or services for prospective purchase. Human beings are perceived as rational actors who intend to plan actions to achieve a certain task and to behave accordingly, which explains that intentions shape human behavior [74,78]. However, Ajzen, Brown, and Carvajal [79] recommended that "investigations that rely on intention as a proxy for actual behavior must be interpreted with caution."…”
Section: Consumer Adoption Intention To Use Ofdo Servicesmentioning
confidence: 99%